Joint Ventures in the People's Republic of China : the Control of Foreign Direct Investment under Socialism. - Pearson, Margaret M. (Princeton University Press, 2001)
When Chinese leaders announced in late 1978 that China would "open to the outside world," they embarked on a strategy for attracting private foreign capital to spur economic development. At the same time, they were concerned about possible negative repercussions of this policy. Margaret Pearson examines government efforts to control the terms of foreign investment between 1979 and 1988 and, more broadly, the abilities of socialist states in general to establish the terms of their own participation in the world economy. Drawing on interviews with Chinese and foreigners involved in joint venture.